Correlation of Quality of Lac (especially Colour) with the Climatic Conditions of the Growing Region - Chopra, S. S.; Sankaranarayanan, Y. (Indian Forester, 1966)
About 40 samples of fresh palas sticklac of various crops during a period of 4 years, were collected from representative regions. And processed into seedlac and shellac. These were analysed for quality under standard conditions, and the data obtained examined in the light of the climatic conditions of the areas in which these stickJacs were produced. Statistical analysis showed no relationship between humidity of the area and colour of the lac produced. However, 'life' under heat of the shellac was higher when the humidity was higher and vice versa.